TECHNOLOGICAL CAPABILITIES OF APPLICATION OF THERMOCYCLIC PROCESSING (TCP) TOOL STEEL - F.R, Norkhudjayev; D. M, Ergashev; M, Ergashev D.; S.T, Djalolova (International Journal of Psychosocial Rehabilitation, 2020)
Thermocyclic processing (TCP) is based on the idea of repeated heating- cooling of steel without exposure at a continuous temperature of heating. At the same time, values of temperatures at the upper and lower levels and the speed of heating of cooling can be constants. The recurrence of thermal influences is caused by aspiration to accumulation in object of structural and phase changes. Unlike traditional heat treatment at TCP each subsequent thermocycle occurs on the basis of a new structural and phase status. It ultimately allows that after the last cycle of TCP or the completing heat treatment began to reach substantial increase of properties, which in combination of different characteristics in many cases is unattainable at traditional heat treatment. In this work the possibility of carrying out TCP not heat resistant tool steel using lubricoolant on the basis of water-soluble polymer of the medicine "Uniflock" is considered.